Adult severe encephalitis/encephalopathy with a reversible splenial lesion of the corpus callosum: A case report. Issue 26 (June 2018) - Mao, Xi-jing; Zhu, Bo-chi; Yu, Ting-min; Yao, Gang
Abstract: Rationale: Clinically mild encephalitis/encephalopathy with a reversible splenial lesion of the corpus callosum (MERS) is a recently identified clinically and radiologically distinct syndrome. Clinical symptoms and lesions on the magnetic resonance imaging (MRI) often disappear in 1 week or a few weeks. However, MERS manifesting as a severe clinical course with significant sequela has not yet been reported. Patient concerns: A 42-year-old male presented with a 3-day history of headache, fever, and irrational speech. Physical examination showed a body temperature of 39.5°C, dysarthria, dyscalculia, recent memory disturbance, and otherwise normal vital signs. The patient developed status epilepticus and progressive consciousness disturbance. MRI showed abnormal patchy signals in the splenium of the corpus callosum. Diagnosis: The clinical feature and the characteristic of MRI are mostly consistent with MERS. At the same time, we made a differential diagnosis by testing the NMDARAb, AMPA1Ab, AMPA2Ab, LG1Ab, CASPR2Ab, GABABRAb in CSF and serum. Interventions: The subject was treated with ganciclovir, antiepileptic, and antipyretic therapy. Outcomes: The subject was living a virtually normal life with persistent mild memory disturbance. MRI showed that the abnormal signals in the splenium of the corpus callosum had disappeared, but hyperintensity on T2-weighted and FLAIR imaging was noted in the centrum semiovale. Lessons: MERS is a rare clinicoradiological syndrome, which can manifest as severe symptoms as well. Early diagnosis and treatment should be emphasized, and the diagnostic value of MRI is highlighted. Clinicians should be alert to the potential sequela.